Interventions in reducing anxiety among patients undergoing percutaneous coronary intervention (PCI): an integrated literature review - Effita Piscesiana; Tuti Herawati; Sri Yona (Alma Ata University Press, 2021)
Background: The percutaneous coronary intervention procedure (PCI) is an action to restore reduced coronary artery blood flow due to occlusion or blockage. Complex actions using sophisticated tools with the patient's condition fully aware can cause clients to experience anxiety, both before, during, and after the action. Many patients undergoing PCI experience this symptom of anxiety. These symptoms can lead to activation of the sympathetic nerves, changes in hemodynamic status, to the risk of arrhythmias during or after the procedure. Intervention to reduce anxiety hopefully can stabilize haemodynamic, avoid unwanted effects during and after the procedure, further can also improve the patient's quality of life.Purpose: This integrated literature review aims to find complementary interventions that can be carried out independently to overcome the anxiety experienced among patients undergoing PPCI.Methods: The compiled database was taken from the EBSCO, Scopus, Clinical Key, ProQuest, Science Direct, PubMed, and Cochrane databases, and published in 2015 - 2020 which were then matched with certain specific keywords to get the appropriate articles. A total of 11 selected articles were reviewed and the results were presented in a table. The results of 6 types of intervention were found, almost all of them were significant in reducing anxiety. Next, appraisal of the quality of selected articles is done by using The Critical Appraisal Skills Programme (CASP).Results: There were 11 articles that discussed 6 different forms of intervention in reducing anxiety, including physical therapy (2 articles), relaxation therapy (2 articles), cognitive therapy (2 articles), psychological therapy (1 article), and psychological therapy programs (combined) (1 article) and information / support / counseling (3 articles).Conclusion: This intervention in addition to reducing anxiety can also reduce stress, hemodynamic balance / physiological indicators, reduce pain, improve quality of life and coping mechanisms.